Abysses and Ghosts. Remarks for a Discourse on Anthropocene Hyper-Aesthetics - Stefano Ascari (European Journal of Creative Practices in Cities and Landscapes, 2023)
In reflecting on a possible aesthetic of the Anthropocene, it seems spontaneous to refer first of all to the figurative and visual outcomes that have been produced within the specific reflection on the topic or at least traditionally associated with the representation of global climate change. Just as the definition of Anthropocene has been widely questioned both from a terminological and chronological point of view, the visual contents in fact (well represented by the 2018 exhibition "Anthropocene: Burtynsky, Baichwal, de Pencier") turn out to be partial and in some cases misleading. They are in fact representative, at most, of one of the possible discourses on the aesthetics of the Anthropocene. In order to articulate the theme better and insert these results in a more effective and broader framework, it is necessary to retrace the history of those images and integrate this narrative heritage with aesthetics generated, even if only apparently, outside the context traditionally referred to the Anthropocene.